2017
DOI: 10.1007/s10897-016-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

Large, Prospective Analysis of the Reasons Patients Do Not Pursue BRCA Genetic Testing Following Genetic Counseling

Abstract: Genetic counseling (GC) and genetic testing (GT) identifies high-risk individuals who benefit from enhanced medical management. Not all individuals undergo GT following GC and understanding the reasons why can impact clinical efficiency, reduce GT costs through appropriate identification of high-risk individuals, and demonstrate the value of pre-GT GC. A collaborative project sponsored by the Michigan Department of Health and Human Services prospectively collects anonymous data on BRCA-related GC visits perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 22 publications
(25 reference statements)
4
32
0
Order By: Relevance
“…Across the seven participating CSER projects, rates of decline ranged from 12 to 64%, with a median of 28%. This variation is consistent with a large range of decline rates cited in the literature for non-GS genetic research (Sterling et al 2006) and genetic testing (Asscher and Koops 2010; Hayden et al 2017). The average rate of decline varied for CSER projects recruiting adult (36%, N = 5 projects) vs. pediatric participants (21%, N = 2 projects), and healthy individuals (43%, N = 3 projects) vs. those with a disease phenotype (25%, N = 4 projects).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Across the seven participating CSER projects, rates of decline ranged from 12 to 64%, with a median of 28%. This variation is consistent with a large range of decline rates cited in the literature for non-GS genetic research (Sterling et al 2006) and genetic testing (Asscher and Koops 2010; Hayden et al 2017). The average rate of decline varied for CSER projects recruiting adult (36%, N = 5 projects) vs. pediatric participants (21%, N = 2 projects), and healthy individuals (43%, N = 3 projects) vs. those with a disease phenotype (25%, N = 4 projects).…”
Section: Discussionsupporting
confidence: 86%
“…Several of the reasons cited for declining GS study participation were similar to those cited in the literature in patients being approached for clinical genetic testing and genetic research (Armstrong et al 2003; Asscher and Koops 2010; Hall et al 2005; Hayden et al 2017; Peterson et al 2002; Sterling et al 2006). This includes study logistics which, if addressed, may positively impact GS study enrollment.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Importantly, when offered genetic testing, most patients with ovarian cancer proceed with testing7 36–40 and would prefer to receive genetic testing early on in the course of their disease 36 41. In a recent prospective analysis of >10 000 individuals referred for BRCA1/2 genetic counselling and testing, over 85% of patients with ovarian cancer consented to genetic testing and the most common reason to decline testing was concern about out-of-pocket costs, which is irrelevant in the Canadian context 40. The potential therapeutic impact of genetic testing, the widespread use and broad scope of NGS panels, and the consistently high acceptance of genetic testing among patients with ovarian cancer, makes this population of women uniquely suited to consider alternative methods of genetic counselling.…”
Section: Challenges and Opportunities In Brca1/2 Assessment In Canadamentioning
confidence: 99%
“…Additionally, they showed that nearly 14% of women in Michigan (13.6% or 243 out of 1,611 women) who met the HBOC screening criteria were forced to decline testing because of insufficient insurance coverage. Finally, they illustrated that although some inappropriate testing was occurring in Michigan (approximately 40% of those tested between 2007 and 2011 did not meet screening criteria), it was less common than insurers might have feared (Hayden et al, 2017; MDHHS Cancer Genomics Program, 2012). As noted earlier, national statistics have shown both a recent surge in patient demand for testing (possibly owing to marketing practices of testing laboratories or celebrity disclosures), but also that at-risk women face barriers in accessing screening.…”
Section: Resultsmentioning
confidence: 99%